Pressure sensitive adhesive compositions comprising polymeric amide monomers, articles, and methods

By using amide monomers and other ethylenically unsaturated monomers, an adhesive composition with a lower glass transition temperature is formed, which solves the problem of degradation of flexibility and adhesion properties of the adhesive under low temperature conditions in the prior art, and achieves the effect of low creep compliance and good adhesion properties.

CN119790116APending Publication Date: 2025-04-083M INNOVATIVE PROPERTIES CO
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202380062667.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-07-18
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the existing adhesive compositions, the glass transition temperature (Tg) of acrylamide is high, resulting in a decrease in flexibility and adhesion properties of the adhesive under low temperature conditions.

Method used

Amide monomers, such as amide monomers with a larger number of carbon atoms, are used to form a binder composition with a lower Tg.

Benefits of technology

It achieves low creep compliance and good adhesion properties of the adhesive under low temperature conditions, and is suitable for thermally activated, UV activated and pressure-sensitive adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005289587820000011
    Figure BDA0005289587820000011
  • Figure BDA0005289587820000041
    Figure BDA0005289587820000041
  • Figure BDA0005289587820000042
    Figure BDA0005289587820000042
Patent Text Reader

Abstract

Described are adhesive compositions comprising an amide monomer (e.g., polymerized units) selected from the group consisting of: i) CH2 = CR4C (O) NHC (R1R1) (C (R1R1)) nC (O) XR3; ii) CH2 = CR4C (O) O (CH2) 2NHC (O) NHR3; wherein n is an integer of 0 or 1; r1 is independently selected from the group consisting of hydrogen, alkyl having 1 to 10 carbon atoms, aryl and alkylaryl; r3 is a group comprising 1 to 30 carbon atoms; R4 is H or CH3; and X is O or NH; and at least 50 wt% of one or more other ethylenically unsaturated monomers (e.g., polymerized units).
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Various adhesive compositions are known. US 10,941,321 describes an adhesive composition comprising a second monomer unit of the formula

[0002]

[0003] wherein R1 is hydrogen or methyl. Such second monomer units are derived from the monomers acrylamide or methacrylamide. The amount of the second monomer unit may be up to 10% by weight. It is worth noting that acrylamide has been reported in the literature to have a glass transition temperature (Tg) of 165°C. Summary of the invention

[0004] Industry would find advantages in adhesive compositions that exhibit low creep compliance including other amide monomers having lower Tg.

[0005] In some embodiments, an adhesive composition is described, the adhesive composition comprising:

[0006] An amide monomer (e.g., a polymerization unit of), the amide monomer (e.g., a polymerization unit of) is selected from the group consisting of:

[0007] i) CH2=CR 4 C(O)NHC(R 1 R 1 )(C(R 1 R 1 )) n C(O)XR 3 ;

[0008] ii) CH2=CR 4 C(O)O(CH2)2NHC(O)NHR 3 ;

[0009] Where n is an integer of 0 or 1;

[0010] R 1 independently selected from hydrogen, alkyl, aryl and alkylaryl having 1 to 10 carbon atoms;

[0011] R 3 is a group containing 1 to 30 carbon atoms,

[0012] R 4 is H or CH3; and

[0013] X is O or NH; and

[0014] At least 50 weight percent (eg, polymerized units) of one or more other ethylenically unsaturated monomers.

[0015] The adhesive composition may be a heat-activatable adhesive, a UV-activatable adhesive, or a pressure-sensitive adhesive.

[0016] In another embodiment, an article is described that includes a first substrate and a curable or cured layer of an adhesive composition as described herein. The substrate can be, for example, a release liner, a polymer film, or an optical substrate.

[0017] In another embodiment, a method of preparing an article is described, the method comprising forming a laminate comprising a first substrate, a second substrate, and a curable adhesive composition layer as described herein between the first substrate and the second substrate; and exposing the curable adhesive composition layer to (e.g., ultraviolet or visible light) actinic radiation to form a cured adhesive composition layer.

[0018] The amide monomers of i) and ii) generally contain an alkylene (or olefin) moiety having a greater number of carbon atoms than acrylamide or methacrylamide. The presence of this moiety can provide better compatibility with low Tg monomers and tend to provide an adhesive composition with a lower Tg. DETAILED DESCRIPTION

[0019] Adhesive compositions prepared by polymerizable compositions are currently described, and the polymerizable compositions include at least two ethylenically unsaturated monomers, one or more amide monomers and one or more other (i.e. different) ethylenically unsaturated monomers. In some embodiments, the adhesive composition can be (e.g., homogeneous) mixture of monomers, such as in the case of liquid (optically transparent) adhesive. In other embodiments, the adhesive composition can include random (meth) acrylic polymers formed by (e.g., homogeneous) mixtures of partially cured monomers. In other embodiments, the adhesive can include (e.g., homogeneous) mixtures of fully cured monomers.

[0020] Amide monomers include ethylenically unsaturated groups, terminal groups including 2 to 30 carbon atoms, and (e.g., continuous) amide groups between the ethylenically unsaturated groups and the terminal groups. The amide group has a nitrogen atom attached to a carbonyl group. In some embodiments, the amide group is part of a urea group. Such amides have two -NH2 groups connected by a carbonyl group (C=O).

[0021] The second amide monomer generally has a structure according to the following formula:

[0022] i) CH2=CR 4 C(O)NHC(R 1 R 1 )(C(R 1 R 1 )) nC(O)XR 3 ;

[0023] ii) CH2=CR 4 C(O)O(CH2)2NHC(O)NHR 3 ;

[0024] Where n is an integer of 0 or 1; R 1 R is independently selected from hydrogen, alkyl, aryl and alkylaryl; 3 is a group containing 2 to 30 carbon atoms; R 4 is H or CH3; and X is O or NH.

[0025] R 3 Typically, it is an alkyl, olefin, aryl, alkylaryl, or ether. As used herein, "alkylaryl" refers to a divalent alkylene group bonded to a terminal aryl group or a divalent arylene group bonded to a terminal alkyl group. 3 Examples of include, for example, benzyl, phenethyl, phenoxyethyl, phenylpropyl, butyl, pentyl, hexyl, octyl, dodecyl, octadecyl, and phenylbutyl. The alkyl group or olefin group may be straight chain, branched, or contain an alicyclic portion. In some embodiments, the terminal group R 3 May contain at least 3 or 4 carbon atoms. In some embodiments where low haze is desired, R 3 is a (e.g., straight chain) hydrocarbon that may contain less than 12, 11, 10, 9, or 8 carbon atoms. However, branched chain hydrocarbons may have better compatibility and thus also provide low haze.

[0026] In some embodiments, R 1 has no more than 10, 9, 8, 7, 6, 5, 4, 3, 2 or 1 carbon atoms. 1 Most typically are aliphatic, such as in the case of hydrogen, methyl or ethyl. In other embodiments, R 1 It is phenyl.

[0027] The monomers can be synthesized at room temperature by a nucleophilic reaction between alkenyl azlactones and primary amines or alcohols as described in Rasmussen et al., US 10,807,069; incorporated herein by reference.

[0028] Representative monomers according to i) are as follows:

[0029] CH2=CHC(O)NHC(CH3)(CH3)C(O)NH(CH2)4C6H5;

[0030] CH2=CHC(O)NHC(CH3)(CH3)C(O)O(CH2)4C6H5;

[0031] CH2=CHC(O)NHC(CH3)(CH3)C(O)NHCH2C6H5;

[0032] CH2=CHC(O)NHC(CH3)(CH3)C(O)NH(CH2)2C6H5;

[0033] CH2=CHC(O)NHC(CH3)(CH3)C(O)NH(CH2)2OC6H5;

[0034] CH2=CHC(O)NHC(CH3)(CH3)C(O)NH(CH2)3C6H5;

[0035] CH2=CHC(O)NHC(CH3)(CH3)C(O)NH(CH2)3CH3;

[0036] CH2=CHC(O)NHC(CH3)(CH3)C(O)NH(CH2)5CH3;

[0037] CH2=CHC(O)NHC(CH3)(CH3)C(O)NH(CH2)7CH3;

[0038] CH2=CHC(O)NHC(CH3)(CH3)C(O)NH(CH2) 11 CH3;

[0039] CH2=CHC(O)NHC(CH3)(CH3)C(O)NH(CH2) 17 CH3.

[0040] Representative (eg urea) monomers according to ii) are as follows:

[0041] The adhesive may contain only amide monomers according to formula i), amide monomers according to formula ii), or combinations of such amide monomers. Combinations include at least two amide monomers of formula i), at least two amide monomers of formula ii), and a combination of at least one amide monomer of formula i) and at least one amide monomer of formula ii).

[0042]

[0043] The adhesive composition typically comprises at least 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, or 5 wt% of (e.g., polymerized units) or amide monomers according to i), ii), or mixtures thereof, based on the total amount of ethylenically unsaturated (e.g., free radical) polymerizable or polymerizable components of the adhesive composition. The amount of i), ii), or mixtures thereof is typically no greater than 30 wt%, 25 wt%, 20 wt%, 15 wt%, 10 wt%, or 5 wt%.

[0044] In typical embodiments, the adhesive composition generally contains little or no acrylamide monomer or methacrylamide monomer (e.g., polymerized units of). Thus, the adhesive composition contains little or no polymerized units having the formula

[0045]

[0046] Thus, the amount of such monomers or polymerized units thereof is zero or less than 0.05, 0.01 or 0.001 weight percent of the total amount of ethylenically unsaturated (eg, free radically) polymerizable or polymerizable components of the adhesive composition.

[0047] The adhesive composition comprises one or more other ethylenically unsaturated monomers (i.e., different from i) and ii). The amount of the other ethylenically unsaturated monomers is typically at least 70% by weight and no more than 99.5% by weight of the total amount of (e.g., polymerized units) of the ethylenically unsaturated (e.g., free radical polymerizable) components of the adhesive composition. Inorganic fillers and non-polymerizable organic components such as plasticizers, tackifiers, and organic fillers are not part of the ethylenically unsaturated polymerizable or polymerized components of the adhesive composition. In some embodiments, the amount of the other ethylenically unsaturated monomers is at least 70%, 75%, 80%, 85%, 90%, 95%, or 99.5% by weight of the total amount of (e.g., polymerized units) of the ethylenically unsaturated (e.g., free radical polymerizable) components of the adhesive composition. In some embodiments, the amount of other ethylenically unsaturated monomers is no greater than 99.5 wt%, 95 wt%, 90 wt%, 85 wt%, 80 wt%, 75 wt%, or 70 wt% of the total amount of ethylenically unsaturated (e.g., free radical polymerizable) components (e.g., polymerized units) of the adhesive composition.

[0048] In some embodiments, the other ethylenically unsaturated monomers include a "(meth)acryloyl" group of the formula H2C=CR1-(CO)-, wherein R1 is hydrogen or methyl, such as (meth)acrylate. The polymerized unit of the (meth)acrylate monomer may be represented by the following formula (I).

[0049]

[0050] In formula (I), R1 is hydrogen or methyl, and R2 is an alkyl, heteroalkyl, aryl, aralkyl or alkaryl group. In other words, the first monomer unit is derived from alkyl (meth) acrylate, heteroalkyl (meth) acrylate, aryl (meth) acrylate, aralkyl (meth) acrylate, alkaryl (meth) acrylate or a mixture thereof (i.e., the (meth) acrylate copolymer may have a plurality of first monomer units with different R2 groups). Suitable alkyl R2 groups typically have 1 to 32 carbon atoms, 1 to 24 carbon atoms, 1 to 18 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 10 carbon atoms, 1 to 8 carbon atoms, 1 to 6 carbon atoms or 1 to 4 carbon atoms. The alkyl group may be linear, branched, cyclic or a combination thereof. Suitable heteroalkyl R 2 The group generally has 1 to 30 carbon atoms or more and 1 to 20 carbon atoms or more, 1 to 20 carbon atoms and 1 to 10 heteroatoms, 1 to 16 carbon atoms and 1 to 8 heteroatoms, 1 to 12 carbon atoms and 1 to 6 heteroatoms or 1 to 10 carbon atoms and 1 to 5 heteroatoms.Heteroatoms are generally oxygen (oxy groups), but can be sulphur (-S- groups) or nitrogen (-NH- groups).Suitable aryl R2 groups are generally carbocyclic aromatic groups.Aryl groups generally have 6 to 12 carbon atoms or 6 to 10 carbon atoms.In many embodiments, aryl is phenyl.Suitable aralkyl groups have formula-R-Ar, wherein R is alkylene and Ar is aryl. Alkylene group, it is the divalent group of alkane, usually has 1 to 10 carbon atoms, 1 to 6 carbon atoms or 1 to 4 carbon atoms, and aryl group usually has 6 to 12 carbon atoms, 6 to 10 carbon atoms or 6 carbon atoms.In many embodiments, aryl is phenyl.Suitable alkaryl group has formula-Ar-R, wherein Ar is arylene (i.e. the divalent group of carbocyclic aromatic compound) and R is alkyl.Arylene usually has 6 to 12 carbon atoms, 6 to 10 carbon atoms or 6 carbon atoms.In many embodiments, arylene is phenylene.The alkyl group of alkaryl group is identical with the above description for alkyl group, but usually has 1 to 10 carbon atoms, 1 to 6 carbon atoms or 1 to 4 carbon atoms.

[0051] The R2 group in formula (I) is typically an alkyl group. In other words, the first monomer unit is typically derived from (i.e., formed from) an alkyl (meth)acrylate. Exemplary alkyl (meth)acrylates typically include, but are not limited to, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, 2-methylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 4-methyl-2-pentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-methylhexyl (meth)acrylate, n-octyl (meth)acrylate , isooctyl (meth)acrylate, 2-octyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, 2-propylheptyl (meth)acrylate, isotridecyl (meth)acrylate, isostearyl (meth)acrylate, octadecyl (meth)acrylate, 2-octyldecyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, and heptadecyl (meth)acrylate. Some branched alkyl (meth)acrylates are (meth)acrylates of Guerbet alcohols having 12 to 32 carbon atoms, as described in 8,137,807 (Clapper et al.). In some embodiments, alkyl (meth)acrylates having an alkyl group containing no more than 8 carbon atoms are selected. These alkyl (meth)acrylates generally have higher solubility parameters than those having an alkyl group containing more than 8 carbon atoms. This can increase compatibility with the amide monomers.

[0052] The group R2 can be a heteroalkyl, aryl, aralkyl or alkaryl group. The example of the monomer with heteroalkyl (e.g., ether) group includes but is not limited to ethoxyethoxyethyl (meth)acrylate, polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate and tetrahydrofurfuryl acrylate. The example of the monomer with aralkyl group includes but is not limited to 2-phenylethyl acrylate, 3-phenylethyl acrylate and 2-biphenylethyl acrylate.

[0053] In other embodiments, the binder may include (e.g., polymerized units of) vinyl monomers. Representative vinyl monomers include, for example, vinyl esters (e.g., vinyl acetate and vinyl propionate), styrene, substituted styrenes (e.g., α-methylstyrene), vinyl halides, N-vinyl pyrrolidone, N-vinyl caprolactam, and mixtures thereof.

[0054] In some embodiments, the adhesive composition comprises polar monomers (e.g., polymerized units of) that include monomers comprising one or more hydroxyl groups, monomers comprising one or more heteroalkyl (e.g., ether) groups, nitrogen-containing monomers (i.e., in addition to i) and ii)), and acidic monomers.

[0055] In some embodiments, the adhesive composition generally includes at least 10 wt%, 15 wt%, 20 wt%, or 25 wt% of the total amount of polar monomers (e.g., polymerized units) of the ethylenically unsaturated (e.g., free radical polymerizable) components of the adhesive composition. In some embodiments, the amount of polar monomer is no more than 50 wt%, 45 wt%, 40 wt%, 35 wt%, 30 wt%, 25 wt%, 20 wt%, 15 wt%, or 10 wt%. Adhesive compositions with sufficiently low amounts of polar monomers may have better compatibility with amide monomers of i) or ii) that have longer chain length alkyl groups, such as C12 or longer.

[0056] In some embodiments, the polar monomer comprises one or more hydroxyl groups.Representative monomers include hydroxy-substituted alkyl (meth) acrylates, hydroxy-substituted alkyl (meth) acrylamides, hydroxy-substituted heteroalkyl (meth) acrylates and hydroxy-substituted heteroalkyl (meth) acrylamides.Examples of hydroxy-substituted alkyl (meth) acrylates include but are not limited to 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 3-hydroxypropyl (meth) acrylate and 4-hydroxybutyl (meth) acrylate.Hydroxy-substituted alkyl (meth) acrylamides include but are not limited to 2-hydroxyethyl (meth) acrylamide and 3-hydroxypropyl (meth) acrylamide.Example hydroxy-substituted heteroalkyl (meth) acrylates include hydroxy-terminated oxyalkyl (meth) acrylates, hydroxy-terminated di(oxyalkyl) (meth) acrylates and hydroxy-terminated poly(oxyalkyl) (meth) acrylates.Oxidized alkyl is typically ethylene oxide or propylene oxide. Specific examples of hydroxyl-terminated poly(oxyalkylene) (meth)acrylates include various monomers commercially available from Sartomer, Exton, PA, USA under the trade designations CD570, CD571, and CD572 and from Geo Specialty Chemicals, Ambler, PA, USA under the trade designation BISOMER (e.g., BISOMER PPA 6).

[0057] In some embodiments, the adhesive composition comprises at least 1 wt%, 2 wt%, 3 wt%, 4 wt%, or 5 wt% of a polar monomer having one or more hydroxyl groups (e.g., polymerized units of). In some embodiments, the amount of polar monomer having one or more hydroxyl groups is no greater than 35 wt%, 30 wt%, 25 wt%, 20 wt%, 15 wt%, or 10 wt% of the total amount of (e.g., polymerized units) of the ethylenically unsaturated (e.g., free radical polymerizable) components of the adhesive composition.

[0058] In other embodiments, the adhesive comprises a nitrogen-containing monomer (e.g., a polymerized unit of). Suitable nitrogen-containing monomer units include, for example, monomer units derived from various N-alkyl (meth) acrylamides, and may include N, N-dialkyl (meth) acrylamides, such as N-ethyl (meth) acrylamide and N, N-diethyl (meth) acrylamide, N-isopropyl (meth) acrylamide, and N-octyl (meth) acrylamide. Other monomer units derived from various N,N-dialkylaminoalkyl (meth)acrylates and N,N-dialkylaminoalkyl (meth)acrylamides may be included, such as, for example, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, N,N-diethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylamide, N,N-diethylaminopropyl (meth)acrylate, and N,N-diethylaminopropyl (meth)acrylamide. Other examples include monomer units derived from N-vinyl pyrrolidone, N-morpholino (meth)acrylate, diacetone (meth)acrylamide, and N-vinyl caprolactam. Thus, the adhesive may comprise an ethylenically unsaturated monomer (eg, polymerized units of) comprising a (meth)acrylamide group of formula H2C=CR1-(CO)-NH- which is not acrylamide, methacrylamide, or an amide monomer according to formula i) or ii).

[0059] In some embodiments, the adhesive composition comprises little or no (for example, polymerized) acidic polar monomers.For example, the polymerizable or curable adhesive composition does not contain or substantially does not contain the monomeric unit derived from (meth) acrylic acid (i.e., formed by it).In other embodiments, the polymerizable or curable adhesive composition does not contain or substantially does not contain monomeric units, and these monomeric units have groups that can be easily hydrolyzed to provide acidic groups.For example, the polymerizable or curable adhesive composition does not contain or substantially does not contain the monomeric unit derived from anhydride-containing monomers (for example, maleic anhydride) or vinyl esters (for example, vinyl acetate).Therefore, based on the total amount of the polymerizable organic component or polymerized unit of the cured (meth) acrylic adhesive composition, the amount of such monomers or monomeric units is zero or less than 0.05 weight %, 0.01 weight % or 0.001 weight %.Acid monomers can be corrosive, especially when substrate or goods contain metal.

[0060] Ethylenically unsaturated monomers are typically selected to control the ultimate glass transition temperature (Tg) and shear storage modulus (G') of the adhesive. In many embodiments, the (meth) acrylate is an alkyl acrylate. The use of an alkyl acrylate instead of an alkyl methacrylate typically results in a cured adhesive composition having a lower glass transition temperature and a lower shear storage modulus (G'). The lower glass transition temperature characteristics and the lower shear storage modulus (G') characteristics can provide a pressure-sensitive adhesive (PSA) composition. PSA is an adhesive that meets the Dahlquist standard for viscosity, which means that the shear storage modulus is typically 3×10 when measured at 25°C and 1 Hz (6.28 rad / sec). 5 Pa (300kPa) or less.

[0061] In some embodiments, the adhesive composition comprises at least 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 99.5% by weight of other (e.g., low Tg) ethylenically unsaturated monomers, wherein homopolymers of such monomers have a glass transition temperature (Tg) of less than 25° C. or 0° C. In some embodiments, the adhesive composition comprises no greater than 99.5%, 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, or 30% by weight of low Tg monomers. The pressure sensitive adhesive composition typically includes a sufficient amount of a low Tg ethylenically unsaturated monomer such that the adhesive has a Tg of less than 25°C or 0°C. The Tg of various ethylenically unsaturated monomers are reported in the literature. See, for example, WO2016 / 094277; incorporated herein by reference. .

[0062] In some embodiments, the adhesive composition comprises at least 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 99.5% by weight of other (e.g., higher Tg) ethylenically unsaturated monomers, wherein homopolymers of such monomers have a glass transition temperature (Tg) greater than 25° C. or 50° C. In some embodiments, the adhesive composition comprises no greater than 99.5%, 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, or 30% by weight of the higher Tg monomer. The pressure sensitive adhesives containing higher Tg ethylenically unsaturated monomers may also contain a tackifier, a plasticizer, or mixtures thereof to reduce the Tg and storage modulus of the adhesive composition.

[0063] In some embodiments, the polymerizable or curable adhesive composition comprises (except for photoinitiators) little or (e.g., polymerized) monomers with aromatic groups. Exemplary aromatic monomers include, but are not limited to, 2-phenoxyethyl acrylate (purchased from Sartomer, Exton, Pennsylvania, under the trade name SR339), 2-(phenylthio)ethyl acrylate, 2-phenylphenoxyethyl acrylate (purchased from Double Bond Chemical Ind. Co., Taipei, Taiwan, China), propionic acid (3-phenoxyphenyl) methyl ester (purchased from Miwon Chemicals Co., Korea). These (higher refractive index) monomer units may have a negative impact on optical transparency. Therefore, based on the total amount of polymerizable organic components or polymerized units of the cured (meth) acrylic adhesive composition, the amount of such monomers or monomer units is zero or less than 0.05 wt%, 0.01 wt%, or 0.001 wt%.

[0064] Amide monomers as well as low Tg, high Tg and polar ethylenically unsaturated monomers are typically monofunctional, ie, contain a single (eg, free radically) polymerizable group.

[0065] The adhesive composition may also include (e.g., polymerized units) of ethylenically unsaturated monomers containing two or more ethylenically unsaturated (e.g., (meth) acryloyl) groups. These monomers may be added to adjust the crosslink density of the cured (meth) acrylate copolymer. When exposed to ultraviolet or visible light radiation in the presence of a photoinitiator, these monomers may react with the side-group (meth) acryloyl groups of the curable (meth) acrylate copolymer. If added, the amount of these monomeric materials is typically in the range of 0% to 30% by weight of the total amount of (e.g., polymerized) ethylenically unsaturated monomers. This amount may be at least 1%, 2%, 3%, 4%, or 5% by weight of the total amount of (e.g., polymerized) ethylenically unsaturated monomers and not more than 25%, 20%, 15%, or 10% by weight.

[0066] Monomers having two (meth)acryloyl groups include 1,2-ethylene glycol diacrylate, 1,3-propylene glycol diacrylate, 1,9-nonanediol diacrylate, 1,12-dodecanediol diacrylate, 1,4-butylene glycol diacrylate, 1,6-hexanediol diacrylate, butanediol diacrylate, bisphenol A diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, tripropylene glycol diacrylate, polyethylene glycol diacrylate (e.g., available from Sartomer under the trade names SR-210, SR-252, and SR-603), polypropylene glycol diacrylate, polyethylene / polypropylene copolymer diacrylate, hydroxypivalate neopentyl glycol diacrylate modified caprolactone, and diacrylate polyurethane (e.g., available from Sartomer under the trade names CN9018 and CN983).

[0067] Monomers having three or four (meth)acryloyl groups include, but are not limited to, trimethylolpropane triacrylate (e.g., commercially available under the trade name TMPTA from Allnex, Alpharetta, GA, and commercially available under the trade name SR-351 from Sartomer, Exton, Pennsylvania), pentaerythritol triacrylate (e.g., commercially available under the trade name SR-444 from Sartomer), tris(2-hydroxyethyl isocyanurate) triacrylate (e.g., commercially available under the trade name SR-368 from Sartomer), a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (e.g., commercially available under the trade name PETIA(Tetrapter), and ... acrylate to triacrylate ratio of about 1:1) and under the trade name PETA-K (tetraacrylate to triacrylate ratio of about 3:1) from Allnex Corporation), pentaerythritol tetraacrylate (e.g., commercially available under the trade name SR-295 from Sartomer Corporation), di-trimethylolpropane tetraacrylate (e.g., commercially available under the trade name SR-355 from Sartomer Corporation), and ethoxylated pentaerythritol tetraacrylate (e.g., commercially available under the trade name SR-494 from Sartomer Corporation). Exemplary crosslinkers having five (meth)acryloyl groups include, but are not limited to, dipentaerythritol pentaacrylate (e.g., commercially available under the trade name SR-399 from Sartomer Corporation).

[0068] The polymerizable composition typically includes a free radical initiator to start the polymerization of the monomers. The free radical initiator may be a photoinitiator or a thermal initiator. The amount of the free radical initiator is typically in the range of 0.05 wt % to 5 wt % based on the total weight of the monomers used.

[0069] Suitable thermal initiators include various azo compounds such as those commercially available from Chemours (Wilmington, DE, USA) under the trade name VAZO, including VAZO 67 (which is 2,2'-azobis(2-methylbutyronitrile)), VAZO 64 (which is 2,2'-azobis(isobutyronitrile)), VAZO 52 (which is 2,2'-azobis(2,4-dimethylvaleronitrile)), and VAZO 88 (which is 1,1'-azobis(cyclohexanecarbonitrile)); various peroxides such as benzoyl peroxide, cyclohexane peroxide, lauroyl peroxide, di-t-amyl peroxide, t-butyl peroxybenzoate, dicumyl peroxide, and LUPEROX (e.g., LUPEROX 101 (which is 2,5-bis(t-butylperoxy)-2,5-dimethylhexane) and LUPEROX Peroxides commercially available from Arkema (King of Prussia, PA) include 130 (which is 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne); various hydroperoxides, such as tert-amyl hydroperoxide and tert-butyl hydroperoxide; and mixtures thereof.

[0070] In many embodiments, the free radical initiator is a photoinitiator, such as a photoinitiator comprising an aromatic ketone group. When exposed to ultraviolet radiation, the aromatic ketone group can capture hydrogen atoms from another polymer chain or from another part of the polymer chain. This capture leads to the formation of free radicals, which can then combine to form crosslinks between polymer chains or within the same polymer chain. In many embodiments, the aromatic ketone group is an aromatic ketone group such as a derivative of, for example, benzophenone, acetophenone or anthraquinone. Representative photoinitiators include, for example, 4-(meth)acryloxybenzophenone, 4-(meth)acryloxyethoxybenzophenone, 4-(meth)acryloxy-4'-methoxybenzophenone, 4-(meth)acryloxyethoxy-4'-methoxybenzophenone, 4-(meth)acryloxy-4'-bromobenzophenone and 4-acryloxyethoxy-4'-bromobenzophenone.

[0071] Other photoinitiators are benzoin ethers (e.g., benzoin methyl ether or benzoin isopropyl ether) or substituted benzoin ethers (e.g., anisole methyl ether). Other photoinitiators are substituted acetophenones, such as 2,2-diethoxyacetophenone or 2,2-dimethoxy-2-phenylacetophenone (commercially available under the trade name Omnirad BDK from IGM Resins Inc. (Charlotte, NC, USA) or under the trade name ESACURE KB-1 from Sartomer, Exton, Pennsylvania, USA). Still other photoinitiators are substituted α-ketols (such as 2-methyl-2-hydroxypropiophenone), aromatic sulfonyl chlorides (such as 2-naphthalenesulfonyl chloride) and photoactive oximes (such as 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime). Other suitable photoinitiators include, for example, 1-hydroxycyclohexyl phenyl ketone (commercially available under the trade name Omnirad 184), bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (commercially available under the trade name Omnirad 819), ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate (commercially available under the trade name Omnirad TPO-L), 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one (commercially available under the trade name Omnirad 2959), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone (commercially available under the trade name Omnirad 369), 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (commercially available under the trade name Omnirad 400), 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1- ...methylthio)phenyl]-2-morpholinopropan-1-one (commercially available under the trade name Omnirad 400), 1-[4-(2-methylthio)phenyl]-2-morpholinopropan-1-one (commercially available under the trade name Omnirad 400), 1-[4-(2-methylthio)phenyl]-2-morpholinopropan-1-one (commercially available under the trade name Omnirad 400), 1-[4-(2 The polymerizable composition may optionally further comprise a chain transfer agent to control the molecular weight of the cured adhesive. Examples of useful chain transfer agents include, but are not limited to, carbon tetrabromide, alcohols (e.g., ethanol and isopropanol), mercaptans or thiols (e.g., lauryl mercaptan, butyl mercaptan, tert-dodecyl mercaptan, ethyl mercaptan, isooctyl thioglycolate, 2-ethylhexyl thioglycolate, 2-ethylhexyl mercaptopropionate, ethylene glycol bisthioglycolate), and mixtures thereof. If used, the polymerizable mixture may comprise up to 1% by weight of the chain transfer agent based on the total weight of the monomers. This amount may be at most 0.5 wt%, at most 0.3 wt%, at most 0.2 wt%, or at most 0.1 wt%, and typically equals at least 0.005 wt%, at least 0.01 wt%, at least 0.05 wt%, or at least 0.1 wt%.For example, the polymerizable composition can comprise 0.005 wt% to 0.5 wt%, 0.01 wt% to 0.5 wt%, 0.05 wt% to 0.2 wt%, 0.01 wt% to 0.2 wt%, or 0.01 wt% to 0.1 wt% chain transfer agent, based on the total weight of monomers.

[0072] The polymerizable composition may also include other components such as, for example, antioxidants and / or stabilizers such as hydroquinone monomethyl ether (p-methoxyphenol, MeHQ), and those commercially available from BASF Corp. (Florham Park, NJ, USA) under the trade name IRGANOX 1010 (tetrakis(methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate))methane). If used, antioxidants and / or stabilizers are typically used in an amount ranging from 0.01 wt % (weight percent) to 1.0 wt %, based on the total weight of the monomers in the polymerizable composition.

[0073] The polymerization of the polymerizable composition can be carried out in the presence or absence of an organic solvent. If an organic solvent is included in the polymerizable composition, the amount is usually selected to provide the desired viscosity to the polymerizable composition and the polymer composition. Examples of suitable organic solvents include, but are not limited to, methanol, tetrahydrofuran, ethanol, isopropanol, heptane, acetone, methyl ethyl ketone, methyl acetate, ethyl acetate, toluene, xylene, and ethylene glycol alkyl ethers. Those solvents can be used alone or in combination as a mixture. In some embodiments, based on the gross weight of the polymerizable composition, the organic solvent is present in an amount of less than 15 wt %, less than 10 wt %, less than 8 wt %, less than 6 wt %, less than 5 wt % or less than 2 wt %. If used, any organic solvent is usually removed during the completion of the polymerization reaction or coating. In many embodiments, the polymerization is carried out in the presence of less or no organic solvent. That is, the polymerizable composition does not contain an organic solvent or contains a minimum amount of an organic solvent.

[0074] The monomers may be polymerized by conventional polymerization methods such as solution polymerization or emulsion polymerization, including thermal bulk polymerization under adiabatic conditions, as disclosed in U.S. Pat. Nos. 5,637,646 (Ellis) and 5,986,011 (Ellis et al.). Other methods include solventless bulk polymerization as described in U.S. Pat. Nos. 4,181,752 (Martens et al.), continuous free radical polymerization methods as described in U.S. Pat. Nos. 4,619,979 and 4,843,134 (Kotnour et al.), and polymerization within a polymer package as described in U.S. Pat. No. 5,804,610 (Hamer et al.).

[0075] Adhesive compositions comprising partially or completely cured monomers are sufficiently tacky, which can be characterized by peel strength. If desired, a tackifier can be added to the adhesive composition. Available tackifiers include, for example, rosin ester resins, aromatic hydrocarbon resins, aliphatic hydrocarbon resins and terpene resins. Generally speaking, light-colored tackifiers preferably selected from hydrogenated rosin esters, hydrogenated terpenes or hydrogenated aromatic hydrocarbon resins.

[0076] Low molecular weight polymers derived from (meth)acrylates may optionally be combined with the (meth)acrylate copolymers. Suitable low molecular weight polymers are described, for example, in U.S. Pat. Nos. 6,783,850 (Takizawa et al.), 6,448,339 (Tomita), 4,912,169 (Whitmire et al.), and 6,939,911 (Tosaki et al.). These polymers may be used as tackifiers.

[0077] Plasticizers can also be used to adjust the rheology of the adhesive composition. Plasticizers can be non-reactive compounds such as phosphates, adipates, and phthalates. Various low glass transition temperature (e.g., below 0°C), lower molecular weight (e.g., Mw below 100,000 Daltons as determined by GPC) acrylic polymers prepared similarly to the acrylic tackifiers described above can also be used as plasticizers.

[0078] Other optional additives include, for example, antioxidants, UV stabilizers, UV absorbers, pigments, curing agents, and polymer additives. If desired, these other optional additives may be selected so that they do not significantly reduce the optical clarity of the adhesive composition.

[0079] The physical properties of the partially or fully cured adhesive compositions can be characterized according to the test methods further described in the Examples.

[0080] The adhesive composition typically comprises a lower Tg than the same adhesive comprising polymerized units of (meth)acrylamide monomer in place of the claimed amide monomer. However, the Tg of the adhesive may be greater than the same adhesive without the amide monomer.

[0081] In some embodiments, the final glass transition temperature (Tg) of the (e.g., partially or fully) cured adhesive is at least -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, -10°C, -5°C, 0°C. In some embodiments, the final glass transition temperature (Tg) of the (meth)acrylate copolymer is no greater than 40°C, 35°C, 30°C, 25°C, 20°C, 15°C, 10°C, 5°C, or 0°C. When the Tg exceeds 20°C, the adhesive can be characterized as heat-activatable, i.e., the material becomes sticky and adheres when heated to slightly above the Tg. When cooled below the Tg, these heat-activated adhesives will no longer be sticky, but have sufficient ability to remain on the adherend and have sufficient cohesive strength to be cleanly removed from the adherend. The glass transition temperature of the adhesive can be measured at a frequency of 1 radian / second using a dynamic mechanical analysis as described in the Examples section below.

[0082] In some embodiments, the cured adhesive has a tan delta of less than 1, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, or 0.2 at 70°C. In some embodiments, the cured adhesive has a tan delta of greater than 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, or 0.7 at 70°C.

[0083] In some embodiments, the cured adhesive has a creep compliance of less than 5000 1 / MPa, 4000 1 / MPa, 3000 1 / MPa, 2000 1 / MPa, 1500 1 / MPa, or 1000 1 / MPa at 1000 seconds. In some embodiments, the cured adhesive has a creep compliance of at least 50 1 / MPa, 75 1 / MPa, 100 1 / MPa, 200 1 / MPa, 300 1 / MPa, 400 1 / MPa, or 500 1 / MPa at 1000 seconds.

[0084] In some embodiments, the cured adhesive composition has an average peel of at least 1 N / in, 2 N / in, 3 N / in, 4 N / in, 5 N / in, 10 N / in, 15 N / in, or 20 N / in (2.54 cm). In some embodiments, the cured adhesive composition has an average peel of no more than 40 N / in, 35 N / in, 30 N / in, 25 N / in, or 20 N / in (2.54 cm).

[0085] It should be understood that preferred physical properties may vary depending upon the end use of the bonded article.

[0086] On the other hand, a kind of article is provided, and this article comprises the first substrate and the curable adhesive composition layer adjacent to this first substrate.The curable adhesive composition layer is generally in the form of film.As used herein, term "adjacent" can be used to refer to two kinds of materials, is generally in the form of layer, and it directly contacts or is separated by one or more other materials, such as primer layer or hard coating.Usually, adjacent materials are in direct contact.

[0087] Various methods can be used to form articles. For example, an adhesive composition containing a curable (meth)acrylate copolymer, an optional photoinitiator and any other optional additives can be applied from a solvent or from a melt. Such methods are well known to those skilled in the art. If processed from a coating composition comprising a solvent, a suitable solvent is a solvent that is miscible with the other components of the coating composition. Thus, this means that the coating composition remains homogeneous in a diluted form and during drying so that the components are not separated from the solvent too early. If used, a suitable solvent is a solvent that can be easily removed from the coating. In addition, a suitable solvent is a solvent that will not damage the substrate to which the coating composition is applied (for example, it will not cause cracking of the polymer film). Exemplary solvents include methyl ethyl ketone, methyl isobutyl ketone, 1-methoxy-2-propanol, isopropanol, toluene, ethyl acetate, butyl acetate, acetone, etc. and mixtures thereof.

[0088] In many embodiments, the article comprises a first substrate, a second substrate and a curable adhesive composition layer positioned between the first substrate and the second substrate. The curable (meth) acrylate copolymer in the curable adhesive composition can be cured by exposing the adhesive to heat, ultraviolet or visible radiation or a combination thereof. In some embodiments, the curable adhesive composition is provided in the form of a layer (e.g., film) that can be stored or transported for later curing by a client.

[0089] In some embodiments of the article, the curable adhesive composition layer is a die-cut layer. More specifically, the article may include a die-cut layer positioned between the first substrate and the second substrate. In some specific articles, at least one of the first substrate and the second substrate is a release liner. For example, in some articles, the die-cut layer is positioned between the first release liner and the second release liner. In some other specific articles, the first substrate is a release liner, and the second substrate is an optical substrate (e.g., an optical film).

[0090] On the other hand, a method for preparing an article is provided. The method includes providing a first substrate, a second substrate and a curable adhesive composition layer. The method also includes forming a laminate including a first substrate, a second substrate and a curable adhesive composition layer, wherein the adhesive composition layer is positioned between the first substrate and the second substrate. Still further, the method includes exposing the adhesive composition layer to ultraviolet or visible light radiation to cure the (meth)acrylate copolymer.

[0091] In some examples, adhesive composition can be used for multiple transfer tapes. Transfer tape can be manufactured by applying curable adhesive composition to differential release liner (i.e. double-sided release liner, wherein the two main surfaces of the liner contain release coating, and the release coating is different), and optionally can be at least partially cured. Adhesive composition is usually applied to the side where the liner has a higher release value. After coating, the release liner coated with adhesive is wound into a roller to produce transfer adhesive. Alternatively, adhesive composition is applied to the first liner, and if necessary, dried. The second liner usually having a release value different from the first liner is adjacent to the adhesive positioning relative to the first liner (PSA is positioned between the first liner and the second liner). When unwinding the adhesive transfer tape, the adhesive remains attached to the side where the liner has a higher release value. In use, the transfer adhesive is unwound and laminated to the substrate surface (for example, such as those in the optical related devices disclosed in more detail below, or non-optical related devices and products, such as painted panels, metal panels, window glass, automotive panels, etc.). The transfer adhesive has higher adhesion to the substrate surface than to the release liner and thus transfers from the release liner to the substrate surface.

[0092] Representative examples of optically transparent substrates include glass and polymer substrates including polycarbonates, polyesters (e.g., polyethylene terephthalate and polyethylene naphthalate), polyimides, polyurethanes, poly(meth)acrylates (e.g., poly(methyl methacrylate)), polyvinyl alcohols, polyolefins (e.g., polyethylene, polypropylene, and cyclic olefin copolymers), and cellulose triacetate. Typically, the cover lens can be made of glass, poly(methyl methacrylate), or polycarbonate.

[0093] Suitable liner includes flexible backing materials conventionally used as tape backing, optical film or release liner. Generally speaking, any suitable flexible material can be used, and there is no specific restriction on its refractive index or optical transparency, because it is removed and does not become part of the product including the display substrate. Typical examples of flexible backing materials used as tape backings that can be used for laminates described herein include those made of paper (e.g., kraft paper) or polymer films, such as polypropylene, polyethylene, polyurethane, polyester (e.g., polyethylene terephthalate), ethylene vinyl acetate, cellulose acetate and ethyl cellulose. Some flexible backings may have coatings. For example, the release liner may be coated with a low adhesion component, such as a silicon-containing material or a carbon-containing fluorocarbon material.

[0094] In some preferred embodiments, the adhesive composition that can be cured or solidified is optically transparent.Therefore, some articles can be laminates, and these laminates include optically transparent substrates (for example, optical substrates, such as optical films) and the optically transparent adhesive layer of the solidification or curable adhesive composition of at least one major surface adjacent to the optically transparent substrate.Laminates can also include a second substrate permanently or temporarily attached to the adhesive layer, and wherein the adhesive layer is positioned between the optically transparent substrate and the second substrate.As used herein, optically transparent refers to an adhesive layer (with a thickness of 50 microns), a substrate or a combination thereof with a haze less than 5%, 4%, 3%, 2% or 1%.Adhesive layer, substrate and a combination thereof generally have a visible light transmittance of at least 85% or 90%.Haze and transmittance can be measured according to the test method described in the embodiment.

[0095] Exemplary (e.g., optically transparent) substrates include inorganic substrates such as glass, and organic substrates such as polyethylene terephthalate, cyclic olefin copolymers, polycarbonate, cellulose triacetate, poly(methyl methacrylate), or another polyacrylate. For example, in certain embodiments, the substrate is a lens, a touch sensor, a light emitting display, a light reflecting display, or a polarizer film, or is a portion thereof.

[0096] Exemplary optical substrates include (or are included as part of) a display panel, such as a liquid crystal display, an OLED display, a touch panel, an electrophoretic display, an electrowetting display, or a cathode ray tube, a window or glazing, an optical component, such as a reflector, a polarizer, a diffraction grating, a mirror, or a cover lens, or another film, such as a decorative film or an optical film. In some embodiments, the optical substrate may be optically transparent.

[0097] In some example laminates, an optically transparent adhesive layer (i.e., a cured or curable adhesive composition described herein) is positioned between two substrates, and at least one substrate is an optical film, a display unit, a touch sensor or a lens. The optical film is intended to enhance, regulate, control, maintain, transmit, reflect, refract, absorb, delay or otherwise change the light projected on the surface of the optical film. The optical film included in the laminate includes a material category with optical functions, such as a polarizer, an interference polarizer, a reflective polarizer, a diffuser, a colored optical film, a mirror, a shutter optical film, a light control film, a transparent sheet, a brightening film, an anti-glare and anti-reflection film, etc. The optical film for the provided laminate may also include a delay plate, such as a quarter-wavelength and a half-wavelength phase delay optical element. Other optically transparent films may include anti-crack films and electromagnetic interference filters. These films may also be used as ITO (i.e., indium tin oxide) coatings or patterned substrates, such as those used to manufacture touch sensors.

[0098] In some embodiments, the laminate including the curable or cured adhesive as described herein may be an optical element or may be used to prepare an optical element. As used herein, the term "optical element" refers to an article having an optical effect or optical application. Optical elements can be used, for example, for electronic displays (e.g., liquid crystal displays (LCDs), organic light emitting displays (OLEDs), architectural applications, transportation applications, projection applications, optoelectronic applications, and graphic applications). Suitable optical elements include, but are not limited to, glazing (e.g., windows and windshields), screens or displays, polarizing beam splitters, cathode ray tubes, ITO-coated touch sensors, such as those using glass or light-transmitting plastic substrates, and reflectors.

[0099] The optically clear adhesive composition is suitable for use in electronic display assemblies.

[0100] In some embodiments, the adhesive is suitable for gap filling between an outer cover lens or sheet (e.g., such as those based on glass, polyethylene terephthalate, polycarbonate, poly(methyl methacrylate), cyclic olefin copolymer, etc.) and an underlying display module of an electronic display assembly. The presence of the adhesive improves the performance of the display by reducing the refractive index mismatch between the substrate and the air gap while also providing structural support to the assembly. Filling the gap with an index matching adhesive reduces the reflection of sunlight and ambient light inherent when using a multi-layer display panel; therefore, the contrast and brightness of conventional display panels are improved.

[0101] In some embodiments, an adhesive layer as described herein, as a liquid optically clear adhesive (LOCA) or as an optically clear adhesive film (e.g., a die-cut film, which may be referred to as a contrast enhancement film (CEF)), may be used to assemble the top layer of a display module. For example, during the manufacture of certain display devices, two rigid substrates, such as a liquid crystal display (LCD) and a glass or polycarbonate cover lens, are optically coupled by an adhesive. In many cases, a (e.g., capacitive) touch sensor is also introduced between the LCD and the cover lens.

[0102] In other embodiments, the adhesive is laminated between a printed lens (i.e., a lens having a printed ink step) and a second display substrate. In this embodiment, the curable adhesive composition can conform to a large ink step of the total adhesive (i.e., 20 microns to 100 microns or 50 microns to 100 microns or even higher).

[0103] In addition to various optically related applications and / or electronic display assembly applications, curable and cured adhesive compositions can also be used in a variety of other applications. For example, the article may include a partially (for example, UV) cured adhesive layer (for example, film) on a backing or release liner. If a release liner is used, the layer can be transferred to another substrate. This other substrate can be, for example, a component of an electronic display assembly. That is, the layer can be laminated to another substrate. Usually the film is laminated between the first substrate and the second substrate (that is, the curable adhesive layer is positioned between the first substrate and the second substrate). When partially (for example, UV) cured (for example, pressure-sensitive) adhesive layers can be cured by exposure to heat or light. Once cured, depending on the final modulus, the adhesive layer may or may not be a pressure-sensitive adhesive.

[0104] The present invention is further illustrated by the following examples.

[0105] Example

[0106] Unless otherwise indicated or readily apparent from the context, all parts, percentages, ratios, etc. in the examples and the remainder of the specification are by weight.

[0107] Materials used in the examples

[0108]

[0109]

[0110] Test Method

[0111] Dynamic Mechanical Analysis - Terminal viscosity, glass transition temperature (Tg), and tan δ values ​​were measured in oscillatory shear mode using a TA Instruments rheometer (TA Instruments, Eden Prairie, Minnesota) using adhesive films with a stack thickness of approximately 1 mm. The adhesive film was punched into 8 mm diameter disks and placed between parallel plates. Tg and tan δ were measured by temperature sweep mode (frequency equal to 1 rad / sec), and creep compliance was measured at 25°C under a constant shear stress of 8000 Pa. Creep compliance values ​​were recorded at 1000 s.

[0112] Optical properties: Diffuse transmittance for haze characterization - Adhesive films (100 micrometers thick) were laminated to glass substrates (1 mm thick LCD glass substrates, Swift Glass, Elmira Heights, New York) and the adhesive / glass assembly was placed in the transmission port of the instrument (UltraScan Pro, Hunterlab, USA). Optical properties including haze % values ​​were recorded over the visible wavelength range of 400 nm to 700 nm.

[0113] 180° Peel Adhesion Test - An adhesive film with a thickness of 0.1 mm was laminated on top of a PET film (STCH11, DuPont Teijin Films) with a thickness of 0.05 mm. These adhesive films / PET component films were cut into 0.5-inch strips and laminated on top of a glass substrate. After aging for 1 day, the adhesive film was peeled off at a 180-degree angle using a peel tester (IMASS, Inc., Accord, Massachusetts). The peel speed was set to 12 in / min. Once the peel test was started, the initial results (duration = 2 seconds) were discarded and then recorded for 5 seconds. The final peel force was averaged during this period.

[0114] Preparation Example

[0115] Preparation Example 1: MUC4 (C 11 H 20Synthesis of N2O3) IEM (15 g, 96.7 mmol) was dissolved in CHCl3 (50 g, 418 mmol) in a round-bottom flask with a magnetic stirring bar. BA (7.07 g, 96.7 mmol) was dissolved in CHCl3 (15 g, 126 mmol) in a vial. The IEM solution was set to stir in an ice-water bath and the BA solution was added dropwise. The solution was warmed to room temperature and stirred overnight. The resulting solution was concentrated by rotary evaporation and then vacuum dried to obtain a solid product. The reaction yield was 97%.

[0116] Preparation Example 2: MUC8 (C 15 H 28 Synthesis of N2O3) IEM (5 g, 32.2 mmol) was dissolved in CHCl3 (20 g, 168 mmol) in a round-bottom flask with a magnetic stirring bar. OA (4.17 g, 32.2 mmol) was dissolved in CHCl3 (15 g, 126 mmol) in a vial. The IEM solution was set to stir in an ice-water bath and the OA solution was added dropwise. The solution was warmed to room temperature and stirred overnight. The resulting solution was concentrated by rotary evaporation and then vacuum dried to obtain a solid product. The reaction yield was 99%.

[0117] Preparation Example 3: MUC12 (C 19 H 36 Synthesis of N2O3) IEM (5 g, 32.2 mmol) was dissolved in CHCl3 (20 g, 168 mmol) in a round bottom flask with a magnetic stir bar. DA (5.97 g, 32.2 mmol) was dissolved in CHCl3 (15 g, 126 mmol) in a vial. The IEM solution was set to stir in an ice water bath and the DA solution was added dropwise. The solution was allowed to warm to room temperature and stirred overnight. The resulting solution was concentrated by rotary evaporation and then vacuum dried to obtain a solid product. The reaction yield was 95%.

[0118] Preparation Example 4: AUC4 (C 10 H 18 Synthesis of N2O3) IEA (15.4 g, 109.1 mmol) was dissolved in CHCl3 (30 g, 251 mmol) in a round-bottom flask with a magnetic stirring bar. BA (7.98 g, 109.1) was dissolved in CHCl3 (15 g, 126 mmol) in a vial. The IEA solution was set to stir in an acetone-dry ice bath and the BA solution was added dropwise. The solution was allowed to warm to room temperature and stirred overnight. The resulting solution was concentrated by rotary evaporation and then vacuum dried to obtain a solid product. A white solid was obtained as the final product with a reaction yield of 73%.

[0119] Preparation Example 5: MUC3(C9H 16Synthesis of N2O3) IEM (50 g, 322 mmol) was dissolved in dichloromethane (55 g, 645 mmol) in a 250 mL round bottom flask equipped with a thermocouple, an overhead stirrer, an addition funnel and a dry air inlet. The reaction flask was cooled on an ice-water bath while n-propylamine (19 g, 322 mmol) was added dropwise, keeping the batch temperature below 35°C. The solution was warmed to room temperature and stirred overnight. The resulting solution was concentrated by rotary evaporation and then vacuum dried to give a solid product. The reaction yield was 97%.

[0120] Preparation Example 6: VDM-C4Am (C 11 H 20 Synthesis of N2O2

[0121]

[0122] VDM (10.0 g, 71.9 mmol) was dissolved in 50 mL of EtOAc in a round-bottom flask with a stirring rod, and stirred in a cold water bath. BA (5.256 g, 71.9 mmol) was added dropwise within five minutes. The mixture was then heated to approximately 40 ° C. After 5 minutes at 40 ° C, the mixture was cooled to room temperature and a white solid was crystallized. The solid was filtered, washed with heptane, and dried under vacuum. A white flaky solid was obtained with a reaction yield of 75%.

[0123] Preparation Example 7: VDM-C12Am (C 19 H 36 Synthesis of N2O2) VDM (10.0 g, 71.9 mmol) was dissolved in 75 mL of EtOAc in a round-bottom flask with a stirring bar and set to stir in a cold water bath. DA (13.32 g, 71.9 mmol) was added dropwise over five minutes. The mixture was then heated to about 35°C. After 30 minutes, the mixture was cooled to room temperature and a white solid was crystallized. The collected white solid was washed twice with hexane and then dried under vacuum. The reaction yield was 79%.

[0124] Preparation Example 8: Polymer Preparation

[0125] Polymer compositions SRP-1 and SRP-2 were prepared by partial UV polymerization of a monomer mixture. SRP-1 contained EHA (65 wt%) and THFA (35 wt%) with I651 (0.15 percent, pph). SRP-2 contained EHA (72 wt%), THFA (18 wt%) and EHMA (10 wt%) with I651 (0.15 pph). The output wavelength was 365 nm and the intensity was 0.3 mW / cm 2 Prior to UV light irradiation, the reaction mixture was purged by flowing nitrogen into the jar until a viscous solution of approximately 2,000 cP was obtained.

[0126] Example

[0127] Preparation of Examples E1 to E11 and Comparative Examples CE1 to CE4

[0128] 8 pph of a 20 wt % TPO solution in HEA was added to the polymer composition SRP-1 to obtain a premix SPM-1. An amide or urea monomer solution (20 wt % urea monomer in HEA) was added to SPM-1 according to Table 2, wherein the amount was 100 pph relative to SPM-1. The mixed solution was coated between an RF02N release liner and an RF22N release liner at a coating thickness of 0.1 mm and was heated using an output wavelength of 405 nm (1600 mJ / cm 2 ) light source to further polymerize to form an adhesive film. The adhesive film was tested according to the above test method and the results are in Table 4.

[0129] Preparation of Examples E12 to E20 and Comparative Examples CE5 to CE7

[0130] According to Table 2, an amide or urea monomer solution (20 wt% amide or urea monomer in HEA) was added to SRP-2, wherein the amount was 100 pph relative to SRP-2, to obtain a premix SPM-2. I819 (1 pph) and a 50 wt% solution of allyl-3 in THFA (3 pph) were added to SPM-2, wherein the amount was 100 pph relative to SPM-2. The mixed solution was coated between an RF02N release liner and an RF22N release liner at a coating thickness of 0.1 mm and was heated using an output wavelength of 405 nm (880 mJ / cm 2 ) light source to further polymerize to form an adhesive film. The adhesive film was tested according to the above test method and the results are in Table 4.

[0131] Preparation of Example E21

[0132] A polymer solution was prepared by mixing 234 g 2EHA, 43.6 g 2EHMA, 50.4 g HEA, 32 g MUC3 and 0.22 g HMP in a clear glass jar. The solution was then heated to 365 nm with an output wavelength of 0.3 mW / cm 2 Prior to UV light irradiation, the jar was purged by flowing nitrogen into the jar until a viscous solution of approximately 2,000 cP was obtained. To the polymer solution, 0.36 g of HDDA, 0.9 g of I651, and 0.18 g of GPTMS were mixed into the jar. The mixed solution was coated between an RF02N release liner and an RF22N release liner at a coating thickness of 0.1 mm and was exposed to UV light using an output wavelength of 365 nm (2280 mJ / cm 2 ) light source to further polymerize to form an adhesive film. The adhesive film was tested according to the above test method and the results are in Table 4.

[0133] Table 2. Adhesive compositions

[0134]

[0135]

[0136] * The composition exhibited phase separation and therefore adhesion testing was not performed. However, amide monomers with a C12 group may be compatible in different adhesive compositions containing less polar monomers (eg, THFA, HEA).

[0137] Table 3. Weight % of polymeric composition materials

[0138]

[0139]

[0140] Table 4. Optical, mechanical and adhesive properties of adhesive films

[0141]

[0142] It is noteworthy that the compositions with the amide monomer of i) or ii) have a lower Tg than the same composition with the same amount (wt%) of acrylamide monomer.

Claims

1. An adhesive composition comprising: The polymerized units of amide monomers are selected from the group consisting of: i)CH2=CR 4 C(O)NHC(R 1 R 1 )(C(R 1 R 1 )) n C(O)XR 3 ; ii)CH2=CR 4 C(O)O(CH2)2NHC(O)NHR 3 ; Where n is an integer of 0 or 1; R 1 independently selected from hydrogen or alkyl, aryl and alkylaryl having 1 to 10 carbon atoms; R 3 is a group containing 1 to 30 carbon atoms, R 4 is H or CH3; and X is O or NH; and At least 50% by weight of polymerized units of one or more other ethylenically unsaturated monomers.

2. The adhesive composition according to claim 1, wherein at least 50% by weight of the homopolymer of the other ethylenically unsaturated monomer has a glass transition temperature (Tg) below 25°C.

3. The adhesive composition of claim 1, wherein one or more of the other ethylenically unsaturated monomers have a glass transition temperature greater than 25°C.

4. The adhesive composition according to claim 3, wherein the adhesive composition does not have CH2=CR 4 A polymerized unit of C(O)NH2, wherein R4 is hydrogen or methyl.

5. The adhesive composition according to claims 1 to 4, wherein the adhesive composition further comprises a tackifier, a plasticizer or a mixture thereof.

6. The adhesive composition according to claims 1 to 5, wherein the adhesive further comprises polymerized units of a polar monomer. 7 . The adhesive composition according to claim 6 , wherein the polar monomer comprises a hydroxyl group or an ether group.

8. The adhesive composition according to claim 6, wherein the adhesive has no polymerized units of acidic polar monomers.

9. The adhesive composition of claims 1 to 8, wherein the adhesive comprises up to 30% by weight of polymerized amide monomers.

10. The adhesive composition according to claims 1 to 9, wherein the polymerized amide monomer consists of i).

11. The adhesive composition according to claims 1 to 9, wherein the polymerized amide monomer consists of ii).

12. The adhesive composition of claims 1 to 8, wherein the adhesive at a thickness of 100 microns has a haze of less than 5%, 4%, 3%, 2% or 1%.

13. The adhesive composition according to claims 1 to 12, wherein the adhesive composition is a pressure sensitive adhesive.

14. The adhesive composition according to claims 1 to 13, wherein the adhesive has one or more properties selected from the group consisting of: a) Tg below 25°C or 0°C; b) Tanδ less than 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4 at 70°C; c) creep compliance at 1000 s of less than 5000 1 / MPa, 4000 1 / MPa, 3000 1 / MPa, 2000 1 / MPa or 1500 1 / MPa; d) a peel strength of at least 1 N / inch, 5 N / inch, 10 N / inch, 15 N / inch, 20 N / inch, or 25 N / inch (2.54 cm); and e) A haze of less than 5%, 4%, 3%, 2% or 1%.

15. An article comprising a first substrate and a curable or cured layer of the adhesive composition according to claims 1 to 14.

16. The article of claim 15, wherein the first substrate is a release liner.

17. The article of claims 15 to 16, wherein the first substrate is an organic or inorganic substrate having a haze of less than 5%, 4%, 3%, 2% or 1%.

18. The article of claims 15 to 17, wherein the curable or cured adhesive layer is interposed between the first substrate and the second substrate.

19. A method of preparing an article, the method comprising: forming a laminate comprising a first substrate, a second substrate, and a curable layer of the adhesive composition according to claims 1 to 18 between the first substrate and the second substrate; as well as The curable adhesive composition layer is exposed to ultraviolet or visible radiation to form a cured adhesive composition layer.

20. A polymerizable adhesive composition comprising: An amide monomer, the amide monomer being selected from the group consisting of: i)CH2=CR 4 C(O)NHC(R 1 R 1 )(C(R 1 R 1 )) n C(O)XR 3 ; ii)CH2=CR 4 C(O)O(CH2)2NHC(O)NHR 3 ; Where n is an integer of 0 or 1; R 1 independently selected from hydrogen or alkyl, aryl and alkylaryl having 1 to 10 carbon atoms; R 3 is a group containing 1 to 30 carbon atoms, R 4 is H or CH3; and X is O or NH; and At least 50% by weight of one or more other ethylenically unsaturated monomers.

21. The polymerizable composition of claim 20, wherein the monomer partially cures to form a (meth)acrylic polymer.

22. The polymerizable composition of claims 20 to 21, wherein upon curing, the composition is a pressure sensitive adhesive or a heat activatable adhesive or a UV activatable adhesive.

Citation Information

Patent Citations

  • Hydrophobic monomers, hydrophobically-derivatized supports, and methods of making and using the same

    US10807069B2

  • Curable and cured adhesive compositions

    US10941321B2

  • Acrylic-type pressure sensitive adhesives by means of ultraviolet radiation curing

    US4181752A

  • Continuous free radial polymerization in a wiped-surface reactor

    US4619979A

  • Acrylate pressure-sensitive adhesives containing insolubles

    US4843134A